2000
DOI: 10.1128/jcm.38.12.4653-4654.2000
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Genetic Diversity in Dientamoeba fragilis

Abstract: Uncertainty surrounding the role of Dientamoeba fragilis in human disease could be due in part to the existence of pathogenic and nonpathogenic variants. Evidence for two genetically distinct forms was obtained using PCR-restriction fragment length polymorphism analysis of ribosomal genes. Future studies in humans will need to take D. fragilis diversity into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 10 publications
3
19
0
5
Order By: Relevance
“…It is possible that multiple species or subspecies exist within the genus Dientamoeba and that only certain subtypes are associated with disease. 109,110 Links between the presence or absence of disease and different subtypes have been described in other enteric protozoa. 96 Therefore, this is a plausible explanation for the asymptomatic carriage of Dientamoeba reported in some patients.…”
Section: Genetic Diversity In Dientamoeba and Links To Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that multiple species or subspecies exist within the genus Dientamoeba and that only certain subtypes are associated with disease. 109,110 Links between the presence or absence of disease and different subtypes have been described in other enteric protozoa. 96 Therefore, this is a plausible explanation for the asymptomatic carriage of Dientamoeba reported in some patients.…”
Section: Genetic Diversity In Dientamoeba and Links To Diseasementioning
confidence: 99%
“…It is reported that most patients with genotype 1 experience symptoms while a small minority do not. 6,46,91,109 Only a small amount of data exists for genotype 2. The most recent report of genotype 2 was discussed by Johnson and Clark 109 who isolated the organism into culture media from the stool of a patient with diarrhea.…”
Section: Genetic Diversity In Dientamoeba and Links To Diseasementioning
confidence: 99%
“…No cyst stage is identified yet. Originally, D. fragilis was considered an amoeba, but based on ultra structural characteristics it has been established that it is a trichomonad (Johnson and Clark, 2000;Banik et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Two genotypes have been identified that differ significantly in the sequence of their small subunit ribosomal RNA (SSU rRNA) gene sequences (Johnson and Clark 2000;Peek, Reedeker, and van Gool 2004;Silberman, Clark, and Sogin 1996;Stark et al 2005a;Windsor, Clark, and Macfarlane 2004). However, more than 99% of isolates belong to 1 genotype.…”
mentioning
confidence: 99%